Mulholland Dr. - Lynch, David, 1946-2025; Watts, Naomi; Theroux, Justin; Harring, Laura Elena; Badalamenti, Angelo; Asymmetrical Productions; Universal Studios Home Video (Firm) (Universal City, CA : Universal Home Video, 2002)
A woman comes to Los Angeles to follow her acting career and accidentally takes in an amnesia victim. A close and conflicted relationship begins to develop as the two seek the identity of the anmesia victim.
Originally released as a motion picture in 2001.
Director of photography, Peter Deming; production design, Jack Fisk; editor, Mary Sweeney; music, Angelo Badalamenti.
Naomi Watts, Laura Elena Harring, Justin Theroux, Ann Miller, Robert Forster.
MPAA rating: R.
DVD Dolby digital 5.1 surround stereo.
With English, French and Spanish tracks and French and Spanish subtitles.
Keywords: Motion pictures actors and actresses -- California -- Los Angeles -- Drama; Lesbians -- Drama; Amnesia -- Drama; Detective and mystery films; Video recordings for hard of hearing people; Feature films; Detective films; Mystery films